1993
DOI: 10.1002/ijc.2910550507
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral microvessel density and L53 protein: Correlation with metastasis in head‐and‐neck squamous‐cell carcinoma

Abstract: Squamous-cell carcinoma of the head and neck includes a heterogeneous group of tumours of the upper air and food passages for which prognosis is difficult to assess. In fact, patients in comparable stages may have diverse clinical courses and responses to similar treatments. In order to better define the prognosis of each patient there is therefore a need to identify novel biological markers which reflect more accurately growth rate, progression and metastatic potential of each tumour. We assessed whether meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
141
3
6

Year Published

1996
1996
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(161 citation statements)
references
References 25 publications
11
141
3
6
Order By: Relevance
“…The recent association between vascular density and tumour aggressivity described initially in breast cancer has also been reported in HNSCC (Gasparini et al, 1993). Both the present paper and Van Hoef et al (1993) regarding breast cancer patients have failed to confirm the clinical prognostic relevance of this new parameter.…”
Section: Histobiological Studiescontrasting
confidence: 47%
“…The recent association between vascular density and tumour aggressivity described initially in breast cancer has also been reported in HNSCC (Gasparini et al, 1993). Both the present paper and Van Hoef et al (1993) regarding breast cancer patients have failed to confirm the clinical prognostic relevance of this new parameter.…”
Section: Histobiological Studiescontrasting
confidence: 47%
“…Microvessel density has been shown to be an independent parameter of the severity of tumour disease and a predictor of prognosis of breast cancer patients in most but not all studies addressing this issue (Weidner et al, 1991(Weidner et al, , 1992Bosari et al, 1992;Horak et al, 1992;Toi et al, 1993, Axelsson et al, 1995. A similar correlation has also been demonstrated with other human malignancies, including head and neck squamous cell carcinoma (Gasparini et al, 1993), lung adenocarcinoma (Yamazaki et al, 1994), rectal carcinoma (Saclarides et al, 1994), testicular germ cell tumours (Olivarez et al, 1994), prostate cancer , tumours of the oral cavity (Williams et al, 1994) and gastric carcinoma (Maeda et al, 1995 rie receptor in breast cancer P Salven et al higher when staining was performed using the clone 7E8 antibody (Table I). No specific staining was observed when the sections were incubated with antigen-blocked antibody instead of the primary antibodies, or with the peroxidaseconjugated secondary antibody only.…”
mentioning
confidence: 69%
“…The prognostic role of MC has been widely reported in several types of solid human cancer, such as mammary (Weidner et al, 1991), head and neck (Gasparini et al, 1993), prostate , ovarian (Hollingsworth et al, 1995), colorectal (Saclarides et al, 1994), testicular (Olivarez et al, 1994), urotelial (Uaeger et al, 1994), cutaneous (Barnhill et al, 1992), nervous (Li et al, 1994) and bronchial carcinomas Yamasaki et al, 1994;Fontanini et al, 1995a). These studies, mostly in breast cancers, have shown that intra-tumour microvessel count has an independent prognostic significance when compared with traditional prognostic markers in multivariate analysis (Gasparini and Figure 8 Cytoplasmic VEGF expression in well-differentiated adenocarcinoma of the lung (ABC method; 25 x) Harris, 1995).…”
Section: And Prognosismentioning
confidence: 99%